Leadership styles and job satisfaction among employees in small and medium enterprises - Sakiru, Oladipo Kolapo; Alby, Jeffrey Lawrence D'Silva; Othman, Jamilah; Silong, Abu Daud; Busayo, Adekanye Temitope (Canadian Center of Science and Education, 2013)
Investigation into the relationship between leadership styles and job satisfaction among employees in small and medium enterprises in Nigeria is the main focus of this research. The research used survey design to gather data from one hundred and fifteen employees from the small and medium enterprises.The study utilized simple random sampling techniques and data was collected using a questionnaire that required respondent to rate their level of job satisfactions as well as their “leaders” leadership styles using a five point scale likert type. The result of correlation analysis revealed that the entire leadership styles items are statistically significant at .05 level of significance, also the result of descriptive statistics indicates transformational leadership styles has the most commonly used leadership styles in the small and medium enterprises in Nigeria. Transformational leaders are needed in small and medium scale enterprises in Nigeria to be able to achieve the mission, objectives and goals for the development of this enterprise in the country.